Working in rural areas - the experiences of Umthombo Youth Development Foundation graduates - Andrew J. Ross (AOSIS, 2014)
Background: Recruiting and retaining healthcare professionals (HCPs) for rural areas is challenging throughout the world. Although rural origin HCPs have been identified as being the most likely to work in rural areas, only a small number of rural-origin South African scholars are trained as HCPs each year and many do not return to work in rural areas. Aim: The aim of this article was to present the experiences of rural-origin HCPs who returned to work in a rural area after graduation. Setting: Umthombo Youth Development Foundation has been running an innovating rurally-based scholarship scheme since 1999. By December 2013, 184 students supported by the scheme had graduated and all had returned to work in a rural area for a period of time. Methods: This was a qualitative study using a life history methodology to explore the educational experience of six rural-origin HCPs working in rural areas. Results: The four themes that emerged from the data were: (1) contribution to service delivery; (2) professional development (3) the challenges and frustrations of working in rural hospitals; and (4) the impact of working as an HCP. Conclusion: Rural-origin HCPs are willing to return and work in rural areas. However, context and content factors need to be addressed if a work-back scholarship scheme is to be along-term strategy for the recruitment and retention of HCPs.